Auditoria ambiental de cumplimiento del relleno sanitrio del cantón Pasaje. - Garino Guzmán, Luis Lenin (2013)
The purpose of conducting this environmental audit of compliance with the sanitary landfill of the canton Pasaje means identifying the operational inconsistencies of the environmental management plan and the environmental legal norms, the proposed proposal arises to implement methods.